Phosphine catalyzed addition of long-chain dialkyl phosphites to electron-deficient alkenes. Issue 21 (1st November 2020) - Il'in, Anton; Gubaev, Arthur; Antonova, Anna; Khannanov, Arthur; Galkin, Vladimir
Abstract: Conjugate addition of the long chain dialkyl phosphites to electron-deficient alkenes under PBu3 catalysis afforded the corresponding phosphonates in good yields in a short reaction time. Long chain alkyl groups in the phosphites were well tolerated in this transformation. The products of this reaction are of particular interest as components of lubrication oil composition. Graphical Abstract: